Screening Pyridine Derivatives against Human Hydrogen Sulfide-synthesizing Enzymes by Orthogonal Methods - Zuhra, Karim (2019)
Biosynthesis of hydrogen sulfide (H2S), a key signalling molecule in human (patho)physiology, is mostly accomplished by the human enzymes cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (MST). Several lines of evidence have shown a close correlation between increased H2S production and human diseases, such as several cancer types and amyotrophic lateral sclerosis. Identifying compounds selectively and potently inhibiting the human H2S-synthesizing enzymes may therefore prove beneficial for pharmacological applications. Here, the human enzymes CBS, CSE and MST were expressed and purified from Escherichia coli, and thirty-one pyridine derivatives were synthesized and screened for their ability to bind and inhibit these enzymes. Using differential scanning fluorimetry (DSF), surface plasmon resonance (SPR), circular dichroism spectropolarimetry (CD), and activity assays based on fluorimetric and colorimetric H2S detection, two compounds (C30 and C31) sharing structural similarities were found to weakly inhibit both CBS and CSE: 1 mM C30 inhibited these enzymes by approx. 50% and 40%, respectively, while 0.5 mM C31 accounted for CBS and CSE inhibition by approx. 40% and 60%, respectively. This work, while presenting a robust methodological platform for screening putative inhibitors of the human H2S-synthesizing enzymes, highlights the importance of employing complementary methodologies in compound screenings.